The Burden of Genetic and Epigenetic Traits in Prematurity - Ribeiro de Andrade Ramos, Bruna [UNESP]; da Silva, Márcia Guimarães [UNESP] (Springer Nature, 2018)
Despite decades of investigations and accumulated scientific knowledge, preterm birth (PTB) remains a significant burden worldwide. Several mechanisms have been proposed to explain this condition, and a number of risk factors from infectious to behavioral and genetic/epigenetic factors influence this outcome. The heritability of PTB is estimated to be 17% to 36%, which demonstrates that genetic predisposition plays a key role in PTB. Structural DNA modifications without changes in the DNA sequence and post-transcriptional regulation also have an impact on gene expression and thus influence pregnancy outcomes. There is a complex interplay between environmental factors and the individual’s genetics and epigenetics that may culminate in PTB, but the complete regulatory pathways and networks involved in this context are still unclear. Here, we outline what is known so far about the genetic and epigenetic factors involved in preterm delivery, including polymorphisms, DNA methylation, and microRNAs, and suggest fields for research.
Keywords: DNA methylation; epigenetics; genetics; microRNA; polymorphisms; prematurity; preterm birth